A trusted authentication model for remote users under cloud architecture. (2018) - Song, Yu-xin; Liao, Zhong-xia; Liang, Yan-hua
Trusted computing is principle measure to ensure the security of computing platform, which improves the creditability by functions including data protection, identity authentication, integrity measurement, storage and reports. In order to easily provide architecture for security authentication of terminal members, and to protect the user's privacy and secret data, this article studies the remote identification for TPM. It introduces DAA anonymous authentication technology to traditional PKI and adopts improved DAA scheme to provide trusted identity authentication, secure channel establishment and sub-certificate update operation. We propose a new model for identity authentication under trusted computing environment. The scheme constructs a safe elliptic hyperbola by ISSUER and generate DAA certificate, which awards zero knowledge proof to each platform to achieve DAA certificate respectively. Then the code service provided by OPENSSL is used to establish PCA and simulated the AIK certificate process according to creation of AIK certificate. Finally, the experiments are performed under VMware-workstation and SUSE virtual machines, with TPM Emulator and TPM chips simulation, to verify the feasibility of remote user trustworthiness authentication scheme. The remote authentication scheme focused by this article is a protocol with anonymity, authentication and security, which will be useful and applicable in current information society.